Income of Kijang City Village: Impact of Working Capital, Technology, Experience, and Selling Price - Alamsyahbana, Muhammad Isa; Azura, Wenni Rahma; Chartady, Rachmad; Utami, Ranti (Owner : Riset dan Jurnal Akuntansi, 2024)
The purpose of this research is to determine the influence of working capital, technology, experience, and selling prices on the income of fishermen in the Kijang Kota Village. This study utilizes both primary and secondary data. The research method employed is a quantitative descriptive method. The primary data consists of questionnaires, while secondary data includes records and data from the Central Statistics Agency (BPS). Data collection techniques include questionnaires, documentation, and literature review, with 77 respondents answering a questionnaire containing 53 statements. The data analysis technique involves testing data validity and reliability, classical assumption tests, multiple linear regression tests, and hypothesis testing. The multiple linear regression formula obtained from this research is Y = (0.585) + 0.303X1 + 0.392X2 – 0.144X3 + 0.304X4 + e. The t-test results show calculated t-values of 2.287 for working capital, 5.067 for technology, -1.348 for experience, and 3.244 for selling prices, while the tabulated t-value is 1.993. The F-test results indicate a calculated F-value of 85.191 and a tabulated F-value of 2.73. The coefficient of determination is 0.816, as seen from the Adjusted R Square value. Based on the data analysis results, it can be concluded that working capital, technology, experience, and selling prices, both individually and simultaneously, have an impact on the income of fishermen in the Kijang Kota Village. The influence of these four variables results in an 81.6% increase in the income of fishermen in the Kijang Kota Village, with the remaining percentage being influenced by variables not included in this study.